Electrochemical immunoassay for the detection of antibodies to tick-borne encephalitis virus by using various types of bioconjugates based on silver nanoparticles; Bioelectrochemistry; Vol. 135 - Khristunova E. P. Ekaterina Petrovna; Barek J. Jiri; Kratokhvil B. Bokhumil; Korotkova E. I. Elena Ivanovna; Dorozhko E. V. Elena Vladimirovna; Vyskocil V. Vlastimil (2020, 2020)
Title screen